2019
DOI: 10.3897/mycokeys.56.35204
|View full text |Cite
|
Sign up to set email alerts
|

Updated taxonomy of Lactifluus section Luteoli: L. russulisporus from Australia and L. caliendrifer from Thailand

Abstract: Lactifluusrussulisporus Dierickx & De Crop and Lactifluuscaliendrifer Froyen & De Crop are described from eucalypt forests in Queensland, Australia and different forest types in Thailand, respectively. Both species have recently been published on Index Fungorum and fit morphologically and molecularly in L.sect.Luteoli, a section within L.subg.Gymnocarpi that encompasses species with alboochraceous basidiomes, white latex that stains brown and typical capitate elements in the pileipellis and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…6,9,13 Recent studies demonstrated the feasibility of HME as an alternative continuous formulation strategy to produce crystalline solid dispersions, while improving the dissolution of APIs, an advantage often attributed to amorphous solid dispersions. 1,2,4,6,[19][20][21] Additionally, crystalline solid dispersions present a viable alternative to their amorphous counterparts due to their enhanced stability. 5,6,11,12,17,[21][22][23][24] Yet, the full potential of crystalline solid dispersions has not been achieved possibly due to the lack of understanding of how the crystalline state behaves during the conditions required for HME, particularly those APIs prone to polymorphic phase transformations.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,13 Recent studies demonstrated the feasibility of HME as an alternative continuous formulation strategy to produce crystalline solid dispersions, while improving the dissolution of APIs, an advantage often attributed to amorphous solid dispersions. 1,2,4,6,[19][20][21] Additionally, crystalline solid dispersions present a viable alternative to their amorphous counterparts due to their enhanced stability. 5,6,11,12,17,[21][22][23][24] Yet, the full potential of crystalline solid dispersions has not been achieved possibly due to the lack of understanding of how the crystalline state behaves during the conditions required for HME, particularly those APIs prone to polymorphic phase transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of sampling sites in Southern Europe, none of the more Mediterranean species was found. As the European Lactifluus species have been studied in great detail ( Heilmann-Clausen et al 1998 , Basso 1999 , De Crop et al 2014 , Leonardi et al 2016 , Van de Putte et al 2016 , Delgat et al 2019 , Dierickx et al 2019b ), we did not expect new lineages to emerge, which was indeed the case.…”
Section: Taxonomymentioning
confidence: 77%
“…However, the genus also appears to be well-represented in South America, as new species are being discovered since more South American habitats are being explored ( Henkel et al 2000 , Miller et al 2002 , Smith et al 2011 , Sá et al 2013 , Sá & Wartchow 2013 , Crous et al 2017 , Delgat et al 2019 , Delgat et al 2020 , Duque Barbosa et al 2020 ), and the majority of the proposed South American Lactarius species turns out to belong in Lactifluus ( Pegler & Fiard 1979 , Singer et al 1983 , Miller et al 2002 ). Since 2010, 78 new Lactifluus species have been described: 34 from Asia ( Stubbe et al 2012a , Van de Putte et al 2012 , Wang et al 2012 , Wang et al 2015 , Morozova et al 2013 , Latha et al 2016 , Li et al 2016 , Uniyal et al 2016 , Zhang et al 2016 , Das et al 2017 , Hyde et al 2017 , Song et al 2017 , De Crop et al 2018 , Liu et al 2018 , Song et al 2018 , Bera & Das 2019 , Dierickx et al 2019a , b , Phookamsak et al 2019 ), 16 from Africa ( De Crop et al 2012 , Maba et al 2014 , Maba et al 2015a , b , De Crop et al 2016a, b , De Crop et al 2019 , Delgat et al 2017 , De Lange et al 2018 ), 20 from the Neotropics ( Miller et al 2012 , Montoya et al 2012 , Sá et al 2013 , Sá &...…”
Section: The Genus Lactifluusmentioning
confidence: 99%
See 2 more Smart Citations